Immunotherapy in underrepresented populations of patients with cancer: do we have enough evidence at present? ; A focus on patients with major viral infections and autoimmune disorders - Antonuzzo, Andrea; Calabrò, Fabio; Quaglino, Pietro; Roila, Fausto; Sebastiani, Gian Domenico; Spina, Francesco; Pasqualetti, Giuseppe; Cortinovis, Diego; Tagliaferri, Enrico; Peri, Alessandro; Presotto, Elena Margherita; Egidi, Maria Francesca; et al. (The oncologist, 2020)
The safety and activity of immune checkpoint inhibitors have been characterized in interventional and observational studies. However, only small studies have specifically investigated these agents in patients who are excluded or underrepresented in clinical trials, frequently referred to as “special populations” or “underrepresented populations.” These include older adults, those with dysregulated immune activation, patients with a compromised immune function, and those carrying major viral infections, lymphoproliferative diseases, and major organ dysfunctions. Therefore, there remains substantial uncertainty regarding the use of immune checkpoint inhibitors in these specific settings. The Network of Italian Supportive Care in Oncology has carried out a multidisciplinary project, with the contribution of oncologists and other specialists, to retrieve the existing evidence on the use of immunotherapy in patients with solid and hematological cancers with the final aim to provide an expert guidance. The results of this effort are presented in this article, which is focused on patients with major viral infections or those with immune dysregulation/autoimmune diseases, and could be useful to guide decisions in clinical practice and to design prospective clinical trials focusing on the use of immunotherapy in these populations. Implications for Practice Substantial uncertainty remains regarding the use of immune checkpoint inhibitors in “underrepresented” patients, such as older adults, those with dysregulated immune activation, and patients with a compromised immune function, major viral infections, lymphoproliferative diseases or major organ dysfunctions. The Network of Italian Supportive Care in Oncology has carried out a multidisciplinary project to retrieve the existing evidence on the use of immunotherapy in underrepresented patients with cancer in order provide an expert guidance. The results of this effort, with a focus on patients with major viral infections or those with immune dysregulation/autoimmune diseases, are presented in this article and could be useful to guide decisions both in clinical practice and to design clinical trials.
Gesehen am 28.10.2020